WE ARE HAPPY HERE AND WE WILL STAY, WHAT ABOUT YOU? THE CROSS-LEVEL IMPACT OF EMPLOYEE LOYALTY AND PERFORMANCE ON STUDENT LOYALTY (The South East European Journal of Economics and Business, 2018)
The purpose of this study is to examine links between, on the one hand, employee satisfaction, loyalty and performance, and on the other, the relationship between customer satisfaction and loyalty, as well as their inter-relationship. We conducted a study with employees (53 employees) and students (262 students) across seven departments of a private university in a developing European country. In order to test the cross-level effects of employee-level constructs on student-level constructs, a multilevel analysis was conducted using hierarchical linear modeling. The results confirmed the positive effect of employee satisfaction on employee loyalty and employee performance, but not the impact of the employees’ loyalty on their performances. At the same time, the results showed that students’ satisfaction was positively related to loyalty. Finally, the results showed that, unlike employee performance, employee loyalty at the level of the department had a positive and significant impact on the students’ loyalty and also enhanced the effect of students’ satisfaction on student loyalty.